2020
DOI: 10.7150/thno.45434
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1C hydrogel improves the therapeutic effects of MSCs on colitis in mice through PGE2-mediated M2 macrophage polarization

Abstract: Background: Mesenchymal stem cell (MSC)-based therapies hold great promise for the treatment of inflammatory bowel disease (IBD). In order to optimize and maximize the therapeutic benefits of MSCs, we investigated whether cotransplantation of a chitosan (CS)-based injectable hydrogel with immobilized IGF-1 C domain peptide (CS-IGF-1C) and human placenta-derived MSCs (hP-MSCs) could ameliorate colitis in mice. Methods: IGF-1C hydrogel was generated by immobilizing IGF-1C to CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(57 citation statements)
references
References 48 publications
4
52
0
1
Order By: Relevance
“…As a carrier system with high biocompatibility, biomaterials can improve the survival rate of transplanted cells and can also imitate the ECM microenvironment to provide an ideal niche for implanted cells and drugs [ 56 58 ]. CS have been deeply studied and widely applicated in the field of biomedicine as a natural polymer material with excellent properties [ 29 , 58 ]. Previous studies have confirmed that combining EVs from hP-MSC with injectable CS hydrogel can significantly retain EVs in the ischemic site of hind limbs.…”
Section: Discussionmentioning
confidence: 99%
“…As a carrier system with high biocompatibility, biomaterials can improve the survival rate of transplanted cells and can also imitate the ECM microenvironment to provide an ideal niche for implanted cells and drugs [ 56 58 ]. CS have been deeply studied and widely applicated in the field of biomedicine as a natural polymer material with excellent properties [ 29 , 58 ]. Previous studies have confirmed that combining EVs from hP-MSC with injectable CS hydrogel can significantly retain EVs in the ischemic site of hind limbs.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these hurdles, IFN-γ, TGF-β, IGF-1C, IL-1β, and PGE2 were applied to precondition MSCs before they were administered onto different experimental models, and pretreated MSCs showed an enhanced therapeutic effect, with different limitations [32][33][34][35][36]. All of these promising explorations encouraged us to search further alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Von Kossa (1% silver nitrate) and total collagen staining (1% Sirius Red) were used to identify the mineralized bone. Immunohistochemical and immunofluorescence staining 72 , 73 was used to detect the phenotype differences and the expression of relevant molecules respectively. The following antibodies were used: anti-Trio (1:200, Santa Cruz, sc-28564), anti-Collagen I (1:300, Abcam, #ab21286), Sox-9 (1:100, Santa Cruz, sc-166505).…”
Section: Methodsmentioning
confidence: 99%